Cynegetical development of the French Mediterranean ``matorral'' scrublands: Case of wild ungulates - Maillard, D; Melac, O; Gaudin, J C; Vassant, J (GIBIER FANE SAUVAGE - GAME AND WILDLIFE, VOL 15 (SPECIAL NUMBER PTS 2 AND 3) 1998, 1998)
Since the beginning of the seventies, the marorrals (garrigues, maquis, and holly oak, Quercus ilex, copses) are slowly being colonized by roe deer, Capreolus capreolus, white wild boar; Sus scrofa, populations are stongly increasing. This phenomenon is mainly due to a relative low hunting pressure compared to the potential huntable population, to the disappearance of traditional farming practices (rural abandonment) causing the matorrals to extend, to the compensations paid to farmers since 1969, and to an increase in food resources (ageing of holly oak copses). As for red deer, Cervus elaphus, its population is increasing very slowly: The uncontrolled increase in wild boar populations is causing intolerable damages to farmers, especially in high-quality crops (arboriculture, vines, market-garden crops), which have been expanding since the productive lands in the bottom of the valley are being cultivated and agricultural techniques have improved. In the years to come, the ungulates frequenting the garrigue may become a harvestable resource if the two main sympatric species (wild boar and roe deer) which are occupying areas of some 30,000 ha, are wisely managed and the following parameters are taken into account : - amount of food produced in the habitats (annual mast crops); - damage control by controlled hunting in each massif, and damage prevention (protection or dissuation); - appropriate management of ungulate territories and the effective control of their populations based on hunting bag analyses in the middle and at the end of the hunting season. Most of ail it is important that before applying the ``population/environment/damage{''} model in each massif or management unit, clear management objectives be defined in agreement with the farmers.
IUGB XXIIIrd Congress, LYON, FRANCE, SEP 01-06, 1997
Keywords: roe deer; Sus scrofa; Wild boar; wild ungulate